2011
DOI: 10.1653/024.094.0458
|View full text |Cite
|
Sign up to set email alerts
|

Daily Activity ofScyphophorus acupunctatus(Coleoptera: Curculionidae) Monitored with Pheromone-Baited Traps in a Field of Mexican Tuberose

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In all experiments, more females than males were captured, although the sex ratio for S. acupunctatus on agave plants is 1:1 (Figueroa-Castro et al 2013). Previous studies have reported similar results when trapping this weevil species in agave and Mexican tuberose crops (Ruiz-Montiel et al 2008, López-Martínez et al 2011, Rodríguez-Rebollar et al 2012, Figueroa-Castro et al 2013, Figueroa-Castro et al 2016a. Our results indicate that the synthetic aggregation pheromone could be responsible for attracting more females than males to the traps because traps without pheromone (i.e., agave tissue alone) captured equivalent proportions of females and males.…”
Section: Discussionsupporting
confidence: 79%
“…In all experiments, more females than males were captured, although the sex ratio for S. acupunctatus on agave plants is 1:1 (Figueroa-Castro et al 2013). Previous studies have reported similar results when trapping this weevil species in agave and Mexican tuberose crops (Ruiz-Montiel et al 2008, López-Martínez et al 2011, Rodríguez-Rebollar et al 2012, Figueroa-Castro et al 2013, Figueroa-Castro et al 2016a. Our results indicate that the synthetic aggregation pheromone could be responsible for attracting more females than males to the traps because traps without pheromone (i.e., agave tissue alone) captured equivalent proportions of females and males.…”
Section: Discussionsupporting
confidence: 79%
“…These results agree with those of Ruiz-Montiel et al (2008), who studied trapping of S. acupunctatus in plantations of blue agave and found that pheromone-baited traps captured more females than males. López-Martínez et al (2011) studied the daily activity of S. acupunctatus by using pheromonebaited traps in a commercial field of Mexican tuberose plant P. tuberosa and captured more females than males. Figueroa-Castro et al (2013), working in blue agave plantations in Jalisco, Mexico, found that the sex ratio of S. acupunctatus populations sampled in agave plants was 1:1, but pheromone-baited traps placed in the same plantations captured more females than males.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, 3 types of promising pheromone and food attractant based traps have been tested for monitoring agave weevil in Mexico; on Jalisco State's blue agave, the TOCCI and TOCCIA traps were evaluated by Bravo-Pérez (2009) and Figueroa-Castro (2014). A 20 L container trap was tested by Azuara-Domínguez et al (2014), and a 5 L container trap was tested on P. tuberosa 'Perla' (Asparagaceae) by López-Martínez et al (2011) and García-Ramírez et al (2014).…”
Section: Determining the Best Pheromone-baited Traps For Capturing Scmentioning
confidence: 99%